Chemical analysis of phenolic compounds and determination of antioxidant, antimicrobial and cytotoxic activities of organic extracts of Pinus coulteri - Merah, Soumia; Dahmane, Dahmane; Krimat, Soumeya; Metidji, Hafidha; Nouasri, Ahmed; Lamari, Lynda; Dob, Tahar (Bangladesh Journal of Pharmacology, 2018)
New bioactive natural products, the phenolic composition and the biological activities of organic extracts from the needles of the Algerian Pinus coulteri were investigated. The analysis by HPLC-DAD of crude extract revealed the presence of 10 phenolic acids and nine flavonoids. In vitro anti-oxidant activities were performed using four different tests. The greatest antiradical activity was found in the ethyl acetate fraction (IC50 = 3.2 ± 0.3 µg/mL), whereas the diethyl ether fraction had the higher contents of total phenolics and flavonoids and exhibited a highest activity in reducing power and β-carotene–linoleic acid tests with EC50= 67.1 ± 0.4 μg/mL and 71.5 ± 0.2% of inhibition, respectively. Furthermore, a low to moderate antimicrobial activity according to all extracts was revealed against eight bacteria tested. The MIC value of chloroform fraction showed a strong degree of antibacterial activity (<0.09 mg/mL). The crude extract was found toxic with LC50 value of 15.2 μg/mL by brine shrimp toxicity assay. The needle extract of P. coulteri is rich in valuable biologically active compounds and could represent a new resource of anti-oxidant agents for the treatment of diseases. Video Clip of Methodology: Disc diffusion test: 6 min 41 sec Click to watch